The Relationship of Arm and Wrist Strength to the Velocity of an Open Overhand Volleyball Serve - Braatz, Janelle (My University, 1977)
Arm and wrist strength and the open overhand volleyball serve velocity were determined for 44 female Ss in 7 randomly selected high schools in District III of the Wisconsin Interscholastic Athletic Association. A cable tensiometer and cinematography~were used to determine the S's strength and serving velocity, respectively. Multiple r was used to analyze the collected data and found the relationship between arm and wrist strength and open overhand volleyball serve velocity was P>.05. It was also found that the reliability r coefficient of the arm strength and wrist strength tests .91 and .90, respectively when comparing the higher to lower strength test score.
Keywords: Muscle strength; Arm --Muscles; Volleyball